Does the transformation of high-tech zones into national innovation demonstration zones promote the urban green total factor productivity? - Zhang Tingting; Xie Jiaping; Xie Jiqing; Liang Ling; Bi Lingling (Sustainable Operations and Computers)
The plan of ''transforming national high-tech zones into national innovation demonstration zones (hereinafter referred to as'' NIDZ'') launched in 2009 is an attempt to promote high-quality economic development in China. Based on the quasi-natural experiment of transforming national high-tech zones into NIDZ in 2009, this paper collected and sorted out the data of 51 cities where national high-tech zones were located in China from 2002 to 2018. Then we measured urban green total factor productivity by applying the SBM model and investigated the impact of transformation on urban green total factor productivity through the difference in difference (DID) method. The results show that: (1) Urban green total factor productivity has been improved by transforming into a NIDZ, and the results are relatively stable. (2) Mechanism analysis shows that the promotion of urban green total factor productivity by transformation is realized through green technology innovation and industrial agglomeration mechanism. (3)The heterogeneity analysis shows that the policy effects are better in the developed eastern regions and regions with lower levels of government efficiency, and have not been reflected in the less developed central and western regions and regions with higher levels of government efficiency.